Cantidades crecientes de compost y su efecto en las características agronómicas y rendimiento de pasto Panicum máximum cultivar tanzania en Loreto, Perú- 2022 - Ramirez Tapayuri, Carmen Rosa (2023)
Composting is part of the solution for the management of solid waste in the Amazon region, the Faculty of Agronomy of UNAP is no stranger to this alternative, which is why it presents an investigation called INCREASING AMOUNTS OF COMPOST AND ITS EFFECT ON AGRONOMIC CHARACTERISTICS AND GRASS YIELD Panicum maximum cultivar TANZANIA IN LORETO, PERU- 2022. The evaluations were carried out 45 years after the beginning of the studies, with vegetative seeds (cuttings), in plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 170 m2. With a randomized design of complete blocks (D.B.C.A.), with five treatments and four repetitions, the treatments under study were: T1 (1 ton/ha), T2 (20 ton/ha) of compost, obtaining the following results: A height yield plant of 1.53 m., yield of green matter (kg/m2) and dry matter (kg/m2) of 2.49 kg/m2 and 0.50 kg/m2 respectively. With a plant coverage (%) of 93.50%, leaf/stem ratio (Kg) of 2.30 kg. And a yield of green matter per hectare of 24,900 kg/ha. In this sense, it was shown that, at higher doses of compost, the response is increasing in the dependent variables in the study of the grass Panicum maximum cultivar Tanzania.